Enhanced recovery urinary protocol for patients undergoing hip surgery: a quasi-experimental study - Amoura S Behairy; Manal A Al-Batanony; Emad A Alwashmi; Eglal H Abdel Hakeim (Journal of Infection in Developing Countries)
Introduction: Postoperative urinary retention (POUR) is a common complication after hip surgery. The enhanced recovery urinary protocol (ERUP) is a tool that employs several perioperative strategies to facilitate optimal conditions for surgery and recovery. The aim of this study was to evaluate the effect of ERUP on POUR in patients undergoing hip surgery.